Does high-definition transcranial direct current stimulation change brain electrical activity in professional female basketball players during free-throw shooting? - Moscaleski, Luciane Aparecida; Fonseca, André; Brito, Rodrigo; Morya, Edgard; Morgans, Ryland; Moreira, Alexandre; Okano, Alexandre Hideki (Frontiers in Neuroergonomics, 2022)
Differentiated brain activation in high-performance athletes supports neuronal mechanisms relevant to sports performance. Preparation for the motor action involves cortical and sub-cortical regions that can be non-invasively modulated by electrical current stimulation. This study aimed to investigate the effect of high-definition transcranial direct current stimulation (HD-tDCS) on electrical brain activity in professional female basketball players during free-throw shooting. Successful free-throw shooting (n = 2,361) from seven professional female basketball players was analyzed during two experimental conditions (HD-tDCS cathodic and sham) separated by 72 h. Three spectral bio-markers, Power Ratio Index (PRI), Delta Alpha Ratio (DAR), and Theta Beta Ratio (TBR) were measured (electroencephalography [EEG] Brain Products). Multi-channel HD-tDCS was applied for 20 min, considering current location and intensity for cathodic stimulation: FCC1h, AFF5h, AFF1h (−0.5 mA each), and FCC5h (ground). The within EEG analyses (pre and post HD-tDCS) of frontal channels (Fp1, Fp2, F3, F4, FC1, FC3) for 1 second epoch pre-shooting, showed increases in PRI (p < 0.001) and DAR (p < 0.001) for HD-tDCS cathodic condition, and in TBR for both conditions (cathodic, p = 0.01; sham, p = 0.002). Sub-group analysis divided the sample into less (n = 3; LSG) and more (n = 4; MSG) stable free-throw-shooting performers and revealed that increases in pre to post HD-tDCS in PRI only occurred for the LSG. These results suggest that the effect of HD-tDCS may induce changes in slow frontal frequency brain activities and that this alteration seems to be greater for players demonstrating a less stable free-throw shooting performance.